Women’s Physical Exercise and Gymnastics in Uruguay: Bodies, Gender, and Sexualities in Physical Education Teacher Training in the 1950s - Dogliotti, Paola; Quitzau, Evelise (Historia y Memoria de la Educación, 2023)
In the 1950s, Uruguay had outstanding international recognition at an educational and cultural level and was called “the Switzerland of the Americas”. In this context, the Third Pan-American Congress of Physical Education was held in Montevideo. This article analyses three conferences on women's gymnastics presented at the Congress by prominent Uruguayans. Their writing reveals mainstream understandings of the female sex and the effects generated by physical exercises and various forms of moving over female bodies. Although these sources do not explicitly approach LGBTQ+ people, they condemn (either directly or indirectly) forms of being feminine and masculine that were linked to homosexuality. This paper studies the most recommended bodily practices, adaptations and prohibitions prescribed for women in the mid-twentieth century. These texts were not only published by the National Commission of Physical Education (CNEF), which regulated physical education and sport at the national level; they were also integrated into the curriculum for training physical education teachers in Uruguay during that decade. This study is framed by theoretical references of sex deconstruction, Judith Butler's critique of sex-gender binarism, and Michel Foucault's sexuality device. Finally, it shows how medical knowledge crossed the discourse of sexuality in the field of physical education and supported the justification of the prescriptions of exercises and movements. These recommendations and prohibitions for women were based on the heteronormative sexual matrix, invalidating the existence of LGBTQ+ identities in the realm of physical education and sport